Made-to-Measure Future(s) for Democracy? Views from the Basque Atalaia - Zabalo, Julen; Filibi, Igor.; Escajedo San-Epifanio, Leire; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This open access volume analyses the development of democracy at different levels of governance (from local to global). The Basque search for an institutional and democratic model that adapts to its social needs and solves its problems offers an interesting perspective for analyzing the way in which democracy is seeking new forms of materialization from the local to the global. The volume is divided into four parts. The chapters in Part I analyze the tensions between the neoliberal vision of democracy and the voices contesting it, with projections at different levels of government. The chapters in Part II focus on the emerging framework and scales of Western democracy. The chapters in Part III present new forms of citizen participation, paying special - though not exclusive - attention to new practical strategies for Basque society. The volume concludes with a block of chapters on the relevance of reviewing the methodological and epistemological frameworks from which knowledgeabout democracy and mechanisms of citizen participation is generated (Part IV). By delving deeper into the idea and practice of democratic governance, this volume will be of interest to researchers and students from all disciplines of politics, international relations, sociology and law.
1. Contemplating from the Basque atalaia the challenges posed by the different forms and scales of contemporary deocracy -- 2. The Challenge of Finding a Cosmopolitan Democratic Model -- 3. The neoliberal commercialisation of citizen participation in Spain -- 4. Responses from urban democratization to global neoliberalism -- 5. State Construction and Democratization: The Tasque Union Majority In The Face Of Systemic Exclusion -- 6. Postpandemic Technopolitical Democracy: Algorithmic Nations, Data Sovereignty, Digital Rights, and Data Cooperatives -- 7. The city scale: urbanization and inequality -- 8. Democracy beyond the nation-state: from national sovereignty to pluralist European sovereignty -- 9. The construction of a global democracy through popular participation on the international stage: the case of the International Peoples$1 (BAssembly (IPA) -- 10. Popular power as subject of democratic transformation. A new power for the emergence of communal democracy -- 11. Exploring the right to decide: from a liberal democratic concept to a radical democratic tool. Approaching the Basque case -- 12. Exploring new citizenship practices. The meaning of young activists$1 (Bpolitical engagement in the Basque Country -- 13. Considerations on the democratic challenge from the perspective of social services: community, participation and (in)equality -- 14. Participation, immigration and subjective perception of integration in the Autonomous Community of the Basque Country -- 15. Methodologies for transductive strategies -- 16. Social transformation through supervision in Participatory Action Research -- 17. Exploring analiytical tools for democratic deepening: intersectionality in our research -- 18. Rethinking relationships between public institutions and community initiatives: The cases of Astra (Gernika) and Karmela (Santutxu, Bilbao). .s
Keywords: Europe -- Politics and government; Political science; Political planning; European Politics; Governance and Government; Public Policy